Anticoagulation in syncardia total artificial heart recipients: anti-factor Xa or activated partial thromboplastin time?. (24th November 2021) - Monteagudo-Vela, María; Bowles, Christopher; Raj, Binu; Robinson, Derek; Simon, Andre
Abstract: Although the activated partial thromboplastin time (aPTT) has historically been the method of choice for anticoagulation monitoring in patients undergoing mechanical circulatory support with intravenous unfractionated heparin, it is being progressively superseded by the anti-factor Xa (anti-Xa) method. A retrospective single-arm, single-centre analysis of 20 patients who underwent total artificial heart implantation entailed simultaneous determinations of aPTT and anti-Xa. Agreement between these parameters was assessed using the Bland–Altman method. Despite a positive correlation between aPTT and anti-Xa, normal target ranges were poorly aligned: from 5th to 30th postoperative day, for anti-Xa values of 0.2 and 0.4 U/ml corresponding aPTT values were 52.1 and 65.2 s, 7.9 and 14.8 lower than predicted values, respectively. This was not associated with thromboembolic sequalae. It was not possible to demonstrate a significant relationship between the predictor variables (postoperative day; white blood cell count; C-reactive protein concentration; alanine transaminase and alkaline phosphatase level; bilirubin; haemoglobin; albumin and total protein concentration) and the agreement between aPTT and anti-Xa levels. In summary, when anti-Xa levels were used to guide anticoagulation therapy, corresponding aPTT levels were low with respect to target range. Methodology applied in this study is generalizable to other forms of mechanical circulatory support. Abstract : The activated partial thromboplastin time (aPTT) has been the historical method of choice for anticoagulation monitoring in patients undergoing mechanical circulatory support with intravenous unfractionated heparin (IVUFH).